Does physiological distribution of blood parameters in children depend on socioeconomic status? Results of a German cross-sectional study. Issue 3 (1st March 2018) - Rieger, Kristin; Vogel, Mandy; Engel, Christoph; Ceglarek, Uta; Harms, Kristian; Wurst, Ulrike; Lengfeld, Holger; Richter, Matthias; Kiess, Wieland
Abstract : Objectives: In the present study, we examined the relation between socioeconomic status (SES) and the physiological distribution of iron-related blood parameters. Design: This is a cross-sectional analysis of longitudinal population-based cohort study. Setting: Based on a sample of healthy participants from a German research centre, various blood parameters and values of clinical examinations and questionnaires were collected. Participants: A total of 1206 healthy volunteers aged 2.5 to 19 years, one child per family randomly selected, were included. Primary and secondary outcome measures: Associations between the SES of children by Winkler-Stolzenberg Index (WSI) and its dimensions (income, education, occupation) and iron-related blood parameters (haemoglobin, ferritin and transferrin) were analysed by linear regression analyses. Gender and pubertal stage were included as covariables. Additionally, associations between SES of children by WSI and physical activity (side-to-side jumps, push-ups) as well as body mass index (BMI) were analysed by linear regression analyses. Results: Children with high WSI or family income showed significantly increased z-scores for haemoglobin (P=0.046; P<0.001). Children with increased WSI or family income showed significantly lower z-scores for transferrin (P<0.001). There was a significant correlation between haemoglobin and gender (P<0.001) and between transferrin and pubertal stage (P=0.024). Furthermore, physical activity was positively correlated and BMI was negatively correlated with WSI (P<0.001). Discussion: Our data show an association between SES and the distribution of iron-dependent parameters. Lower SES is correlated with lower values for haemoglobin and higher values for transferrin. Furthermore, we demonstrate that physical activity and BMI are associated with SES. Whereas higher SES is correlated with higher values for physical activity and lower BMI. Our parameters are standardised as z-scores with the advantages that the results are comparable across different age groups and present physiological courses. Trial registration number: NCT02550236 ; Results.